VEHICULAR QUEUE LENGTH MEASUREMENT BASED ON EDGE DETECTION AND VEHICLE FEATURE EXTRACTION - alokaishi, wahban yahya; ZAARANE, ABDELMOGHIT; ATOUF, ISSAM; BENRABH, MOHAMED (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
The queue length is an important parameter used by several companies of traffic management for quantitative analysis of traffic scene. In this paper, we propose a system to measure the queue length. The proposed system contains two principal operations for measuring the queue length the first operation is the motion detection, and the second one is the vehicle detection. The traffic scene is divided into a number of blocks, which have variable sizes based on the camera parameters and the distance between the camera and the position of the block. To minimize the execution time to accord the real-time application, we continuously apply the detection motion operation on the first block of the scene and the queue tail. The vehicle detection algorithm is based on the edge detection and the vehicle features extraction to improve the detection of vehicle and minimize the error of detection of the other things? edges (damaged of road, the mark of the road, the shadow of trees or building). The algorithm is applied to videos obtained by stationary camera. The obtained results demonstrate the robustness and accuracy of the proposed system.